1985
DOI: 10.1161/01.cir.72.5.975
|View full text |Cite
|
Sign up to set email alerts
|

Isometric exercise in patients with chronic advanced heart failure: hemodynamic and neurohumoral evaluation.

Abstract: We evaluated the hemodynamic effects of isometric exercise in 53 patients with congestive heart failure (CHF) and compared them with those found in 10 normal subjects. In both groups, isometric exercise increased heart rate and blood pressure. Systemic resistance increased in patients with CHF (1862 + 520 vs 2126 ± 642 dyne-sec-cm-5; p < .001) but not in normal subjects (1359 + 268 vs 1380 ± 252 dyne-sec-cm-5). Cardiac index and stroke volume index increased mildly but not significantly in the normal subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Nishikawa et al (30) demonstrated that with exercise, left atrial reservoir function increased by 37% and left atrial conduit function decreased by 23%. Although Nishikawa et al did not measure PA pressures, others have demonstrated that substantial pulmonary hypertension can develop during exercise, especially in subjects with abnormal hearts (7,18,23,32). For example, in heart transplant recipients, Pflugfelder et al (32) noted that peak exercise produced a 90% increase in mean PA pressure with a threefold rise in RAP.…”
Section: Discussionmentioning
confidence: 99%
“…Nishikawa et al (30) demonstrated that with exercise, left atrial reservoir function increased by 37% and left atrial conduit function decreased by 23%. Although Nishikawa et al did not measure PA pressures, others have demonstrated that substantial pulmonary hypertension can develop during exercise, especially in subjects with abnormal hearts (7,18,23,32). For example, in heart transplant recipients, Pflugfelder et al (32) noted that peak exercise produced a 90% increase in mean PA pressure with a threefold rise in RAP.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] To date, there are no data on the benefit or harm of a strength or resistance exercise program. Given the threat of complications related to increased myocardial oxygen demand in the face of isometric exercise, 48 patients are usually counseled to avoid lifting a significant weight (eg, Ͼ20 lb) or performing exercises that cause a patient to strain (eg, performing a Valsalva maneuver).…”
Section: Activity and Exercisementioning
confidence: 99%
“…Haemo dynamic response to static exercise was not modified by treatment, though the beneficial effects of NIF at rest were maintained during static exercise. NIF therefore seems to bring baseline haemodynamics back to a very fa vourable level, reducing changes which oc cur in severe CHF patients after isometric exercise while the basic CHF patients re main essentially unchanged [33].…”
Section: Discussionmentioning
confidence: 93%